IL-23 (Interleukin-23)–Producing Conventional Dendritic Cells Control the Detrimental IL-17 (Interleukin-17) Response in Stroke. Issue 1 (January 2018) - Gelderblom, Mathias; Gallizioli, Mattia; Ludewig, Peter; Thom, Vivien; Arunachalam, Priyadharshini; Rissiek, Björn; Bernreuther, Christian; Glatzel, Markus; Korn, Thomas; Arumugam, Thiruma Valavan; Sedlacik, Jan; Gerloff, Christian; et al.
Abstract : Background and Purpose—: Inflammatory mechanisms can exacerbate ischemic tissue damage and worsen clinical outcome in patients with stroke. Both αβ and γδ T cells are established mediators of tissue damage in stroke, and the role of dendritic cells (DCs) in inducing the early events of T cell activation and differentiation in stroke is not well understood. Methods—: In a murine model of experimental stroke, we defined the immune phenotype of infiltrating DC subsets based on flow cytometry of surface markers, the expression of ontogenetic markers, and cytokine levels. We used conditional DC depletion, bone marrow chimeric mice, and IL-23 (interleukin-23) receptor-deficient mice to further explore the functional role of DCs. Results—: We show that the ischemic brain was rapidly infiltrated by IRF4 + /CD172a + conventional type 2 DCs and that conventional type 2 DCs were the most abundant subset in comparison with all other DC subsets. Twenty-four hours after ischemia onset, conventional type 2 DCs became the major source of IL-23, promoting neutrophil infiltration by induction of IL-17 (interleukin-17) in γδ T cells. Functionally, the depletion of CD11c + cells or the genetic disruption of the IL-23 signaling abrogated both IL-17 production in γδ T cells and neutrophil infiltration. Interruption of the IL-23/IL-17 cascade decreased infarct size and improved neurological outcome after stroke. Conclusions—: Our results suggest a central role for interferon regulatory factor 4-positive IL-23–producing conventional DCs in the IL-17–dependent secondary tissue damage in stroke. Abstract : Supplemental Digital Content is available in the text.